If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 + -3x = 12 + -8x Solving 52 + -3x = 12 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 52 + -3x + 8x = 12 + -8x + 8x Combine like terms: -3x + 8x = 5x 52 + 5x = 12 + -8x + 8x Combine like terms: -8x + 8x = 0 52 + 5x = 12 + 0 52 + 5x = 12 Add '-52' to each side of the equation. 52 + -52 + 5x = 12 + -52 Combine like terms: 52 + -52 = 0 0 + 5x = 12 + -52 5x = 12 + -52 Combine like terms: 12 + -52 = -40 5x = -40 Divide each side by '5'. x = -8 Simplifying x = -8
| 9x-(2x-5)=4x+11 | | 8-2(4-x)=2x+5-3 | | 5p^2=12-10p | | 3(-6x+9)10x=1 | | 3m-10=25-4m | | 7(7-x)=133 | | 6x+8=-40-2x | | 3x^2-45x=-168 | | 2x-5y-6z= | | 4.4x-7.8x=21.08 | | x+x+1+x+2+x=192 | | (.25)4y=5(.25) | | 2x+14=-11-3x | | 3x+2y=12y | | 15+g=27 | | 7y-11-10y+3=7 | | -1+49x=21x+43 | | 1/2*2+13=9 | | 9.2(+6.4)=132.48 | | t+13=18 | | -5q+9=-4q | | y=6*x | | x^2+(y^2)+z^2=z | | 5+2(x-3)=8+7 | | q-6=8 | | 18-5x=12-7x | | 2sin(x)tan(x)=3 | | 4x-3y-12z= | | 28y-1=5 | | 5-4y=8 | | 4x^3+4x-4=0 | | 7y-11-10y+3= |